Vector correlations in the reaction O(3P)+CS(X 1Σ+)→CO(X 1Σ+) +S(3P) - Costen, M; Hancock, G; Orr-Ewing, A; Summerfield, D (1994)
The reaction O(3P)+CS(X 1Σ+) →CO(X 1Σ+)+S(3P) has been studied using translationally aligned oxygen atoms formed from the 355 nm polarized photodissociation of NO2. The nascent CO product was detected by laser-induced fluorescence (LIF) with sub-Doppler resolution in order to extract the pair correlations between the reagent and product relative velocities k and k′ and the product rotational angular momentum J′. Previous theories interpreting the Doppler profiles of photodissociation products in terms of vector correlations have been extended to the case of bimolecular reactions. The system studied was seen to yield a close to isotropic distribution of product velocities k′ about the k direction, and a rotational alignment of J′ with k close to zero. The CO molecule departs with its rotational angular momentum vector J′ aligned preferentially perpendicular to the product relative velocity k′, hence exhibiting a negative k′, J′ correlation. Further insight has been gained on these results by quasiclassical trajectory (QCT) calculations on a London-Eyring-Polanyi-Sato (LEPS) potential energy surface (PES). © 1994 American Institute of Physics.